The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bmjspcare-2017-001440
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia: rationale for the MENAC (Multimodal—Exercise, Nutrition and Anti-inflammatory medication for Cachexia) trial

Abstract: Cancer cachexia is a multifactorial syndrome characterized by an on-going loss of skeletal muscle mass that cannot be fully reversed by conventional nutritional support alone. Cachexia has a high prevalence in cancer and a major impact on patient physical function, morbidity and mortality. Despite the consequences of cachexia, there is no licensed treatment for cachexia and no accepted standard of care. It has been argued that the multifactorial genesis of cachexia lends itself to therapeutic targeting through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 63 publications
3
117
0
1
Order By: Relevance
“…Additionally, physical activity seems to be an important element for the treatment of cancer cachexia . Exercise training programs (such as strength and/or aerobic training) demonstrated to have a very clear anti‐inflammatory effect, decreasing pro‐inflammatory cytokines and increasing anti‐inflammatory cytokines .…”
Section: Cancer Cachexiamentioning
confidence: 99%
“…Additionally, physical activity seems to be an important element for the treatment of cancer cachexia . Exercise training programs (such as strength and/or aerobic training) demonstrated to have a very clear anti‐inflammatory effect, decreasing pro‐inflammatory cytokines and increasing anti‐inflammatory cytokines .…”
Section: Cancer Cachexiamentioning
confidence: 99%
“…protein), and pharmacotherapy may be necessary to provide a sufficient stimulus to prevent or slow the cascade of tissue wasting ( Figure 2). 79 Studies to date have focused on the importance of muscle; however, greater attention to the prognostic effects of excess adiposity and the development of interventions with the potential to simultaneously increase muscle and reduce adiposity may be of critical importance. Early intervention to prevent the deterioration of body composition may be more effective than efforts to improve body composition in patients with established cachexia.…”
Section: The Future Of Randomized Clinical Trialsmentioning
confidence: 99%
“…An example of a multimodal intervention that is being tested within an ongoing phase III trial includes non-steroidal anti-inflammatory medication, eicosapentaenoic acid, resistance and aerobic exercise, and dietary counselling with oral nutritional supplements to prevent weight loss and the deterioration of body composition in patients with advanced or metastatic cancer. 79 Studies to date have focused on the importance of muscle; however, greater attention to the prognostic effects of excess adiposity and the development of interventions with the potential to simultaneously increase muscle and reduce adiposity may be of critical importance. Continued efforts to investigate the efficacy of multimodal interventions are urgently needed to advance this area.…”
Section: The Future Of Randomized Clinical Trialsmentioning
confidence: 99%
“…Most of advanced oncologic patients display skeletal muscle wasting associated with functional impairment, and lung cancer patients with cachexia display shorter survival than non‐cachectic ones [35]. In this context, the lack of therapies for cancer cachexia is still evident [36]. By using LLC tumor‐bearing mice, Penna et al (2011) have previously demonstrated that moderate‐intensity aerobic exercise training protocol associated with EPA administration mitigated muscle wasting [20].…”
Section: Discussionmentioning
confidence: 99%